RATIONAL FEEDING STRATEGIES OF SUBSTRATE AND ENZYMES TO ENZYMATIC HYDROLYSIS BIOREACTORS: Scientific paper - Pratto, Bruna; Rodrigues dos Santos-Rocha, Martha Suzana; Batista, Gustavo; Cavalcanti-Montaño, Inti Doraci; Galeano Suarez, Carlos Alberto; Gonçalves Cruz, Antonio José; de Sousa Júnior, Ruy (Chemical Industry & Chemical Engineering Quarterly, 2022)
Bioreactors operating in fed-batch mode improve the enzymatic hydrolysis productivity at high biomass loadings. The present work aimed to apply rational feeding strategies of substrates (pretreated sugarcane straw) and enzymes (CellicCtec2®) to achieve sugar titers at industrial levels. The instantaneous substrate concentration was kept constant at 5% (w/v) along the fed-batch. The enzyme dosage inside the bioreactor was adjusted so that the reaction rate was not less than a pre-defined value (a percentage of the initial reaction rate – rmin). When r reached values below rmin, enzyme pulses were applied to return the reaction rate to its initial value (r0). The optimized feeding policy indicated a reaction rate maintained at a minimum of 70% of r0, based on the trade-off between glucose productivity and enzyme saving. Initially, it was possible to process a 21% (w/v) solid load, achieving 160 g/L of glucose concentration and 80% of glucose yield. It was verified that non-productive enzyme adsorption was the main reason for some reduction of hydrolysis yield regarding the theoretical cellulose-to-glucose conversion. An increment of 30 g/L in the final glucose concentration was achieved when a lignin-blocking additive (soybean protein) was used in the enzymatic hydrolysis.